Can plyometric training change the pacing behaviour during 10-km running?. Issue 1 (2nd January 2023) - do Carmo, Everton C.; Barroso, Renato; Gil, Saulo; da Silva, Natalia R.; Bertuzzi, Romulo; Foster, Carl; Tricoli, Valmor
ABSTRACT: The effects of plyometric training (PT) on middle- and long-distance running performances are well established. However, its influence on pacing behaviour is still unclear. The aim of this study was to evaluate the effects of PT on pacing behaviour. In addition, verify whether the adaptations induced by PT would change ratings of perceived exertion (RPE) and/or affective feelings during the race. Twenty-eight male runners were assigned to two groups: control (C) and PT. PT held two weekly PT sessions for eight weeks. Drop jump (DJ) performance, 10-km running performance, pacing behaviour, RPE and affective feelings, VO2peak, ventilatory thresholds (VT1 and VT2), peak treadmill speed (PTS), and running economy (RE) were measured. For group comparisons, a mixed model analysis for repeated measures, effect size (ES) and 90% confidence interval (90% CI) were calculated for all dependent variables. Significant differences pre-to-post was observed for PT group in DP (7.2%; p  ≤ 0.01; ES = 0.56 (0.28–0.85)) and RE (4.5%; p  ≤ 0.05; ES = −0.52 ((−0.73 to −0.31)) without changes in pacing behaviour. While PT was effective for improving DJ and RE, there is no evidence that pacing behaviour, RPE or affective feelings are directly affected by these adaptations during a 10-km time trial run.